Development of Sigale Gale Statue Tourism Post-COVID-19 Pandemic at Tomok, Samosir Regency - Occy Bonanza; Melewanto Patabang; Dyah Prabandari; Melva Rosalia (Bogor Hospitality Journal, 2025)
The COVID-19 pandemic has led to a decline in tourist visits, significantly impacting the tourism industry, including at Samosir Regency. This region has a prominent tourism sector that is essential for both the government and the local community, with attractions such as the Sigale Gale Statute being affected. The Sigale Gale statue is a unique tourist attraction with the potential to enhance the tourism sector in Samosir Regency. This study explores the history, uniqueness, and management of the Sigale Gale Statue and analyzes the internal and external factors influencing its management to formulate an appropriate development strategy. Data on history, uniqueness, and management were obtained through in-depth interviews, while internal and external data were collected from questionnaires distributed to 200 respondents. Data analysis was conducted using SWOT Analysis with IFAS and EFAS matrices and a SWOT matrix. The analysis results indicate that the development strategy for the Sigale Gale tourism attraction falls in quadrant 4, requiring the implementation of a turn-around strategy. This strategy aims to maximize existing opportunities to mitigate weaknesses in management.